The Effect of Glass Material on The Thermal Comfort of Apartment Unit as A Place to Live: Thermal Comfort of Glass Material - Rafiqa Rahmi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2023)
Indonesia is located on the equator which makes this country have a tropical climate so that it has an influence on the planning of buildings in it, for example apartments. The majority of high-rise apartments in Indonesia use glass curtain walls, but this affects the thermal comfort of the apartment space as a living and active environment, for example in the U-Residence 2 apartment studio unit, Tangerang. Evaluation regarding the use of glass uses a descriptive method with quantitative data based on field observations. From the results of the study it can be concluded that the U-Residence 2 apartment has a thermal environmental performance that tends to be hot and humid so it is necessary to increase the temperature quality mechanically so that it can be declared comfortable.